The single-atom iron nanozyme mimicking peroxidase remodels energy metabolism and tumor immune landscape for synergistic chemodynamic therapy and photothermal therapy of triple-negative breast cancer - Qian, Xiaojun; Shi, Ronghua; Chen, Jian; Wang, Yong; Han, Xinghua; Sun, Yubei; Ling, Cong; Wang, Gang; Xu, An-Wu; Pan, Yueyin (Frontiers in Bioengineering and Biotechnology, 2022)
1.Chemotherapy, as one main strategy to relieve tumor progression, has a weak effect on triple negative breast cancer (TNBC) chest wall metastasis. Development of near infrared (NIR) light-responsive nanomaterials for chemodynamic therapy (CDT) and photothermal therapy (PTT) is a promising platform but still challenging in biomedicine. This study reports a peroxidase mimicking nanozyme (Fe-N-C SAzyme) against TNBC by CDT and PTT. Fe-N-C SAzyme that could decompose H2O2 into hydroxyl radicals (•OH), leading to improvement of reactive oxygen species (ROS) generation and also induce light-to-heat conversion under the exposure of 808 nm laser irradiation. With these biological characteristics, the obtained Fe-N-C SAzymes displayed enhanced cell cytotoxicity and inhibition of cancer cell proliferation both in vitro and in vivo at a low dose of nanoagent and a moderate NIR laser power density. Besides, Fe-N-C nanoagent with its excellent ROS generation brought metabolic reprogramming from oxidative phosphorylation to glycolysis in tumor cells. In vivo experiments, when combined with PTT, the enhanced antitumor effect was found by the elimination of M-MDSC in tumor microenvironment. Fe-N-C SAzymes could serve as a new synergistic CDT and PTT nanoagent, accompanied by metabolic and tumor microenvironment reprogramming. It will provide prospects for chemodynamic/photothermal combined cancer therapy in TNBC chest wall metastasis based on the use of a single nanosystem.